Emerging Electronics Technologies and Solutions for Eco-Friendly Cities - Andriukaitis, Darius; Pan, Yongjun; Brida, Peter (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The growing population is forcing us to look for new, more effective solutions to various problems. The rising demand for power, water supply and waste management, pedestrian safety, the efficient use of electric vehicles, traffic jams, commuting, the identification of all road users and prediction of their travel paths, and increasing air and noise levels are the most pressing issues in today's cities. Advance planning is a feature of green development that reduces dependence on vehicles associated with an increase in greenhouse gas emissions. The development of eco-friendly cities includes the development and application of new efficient solutions and technologies, such as efficient transport management, emission control and pollution control, energy efficiency and the usage of renewable energy, resource efficiency, etc., which would ensure a better quality of life of the growing population.